2011
DOI: 10.1016/j.neuint.2011.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-vasopressin V1a receptor inhibition improves neurologic outcomes following an intracerebral hemorrhagic brain injury

Abstract: Cerebral edema is a devastating consequence of brain injury leading to cerebral blood flow compromise and worsening parenchyma damage. In the present study, we investigated the effects of arginine-vasopressin (AVP) V 1a receptor inhibition following an intracerebral hemorrhagic (ICH) brain injury in mice and closely assessed the role it played in cerebral edema formation, neurobehavioral functioning, and blood-brain-barrier (BBB) disruption. To support our investigation, SR49059, an AVP V 1a receptor competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 39 publications
0
51
0
1
Order By: Relevance
“…And, animal tests have found that AVP receptors antagonist SR49059 significantly decreases cerebral edema at 24 and 72 h post-ICH injury and improved neurobehavioral deficits at 72 h [51] . So, AVP receptors may play an important role in the formation of edema after ICH through reduced BBB permeability or AQP4 levels, but the details of the mechanism are still unknown [52] . An in vivo microdialysis study shows that glutamate, taurine and asparagines accumulate transiently in extracellular fluids in the perihematoma region during the early period of ICH.…”
Section: Rbc Lysis Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, animal tests have found that AVP receptors antagonist SR49059 significantly decreases cerebral edema at 24 and 72 h post-ICH injury and improved neurobehavioral deficits at 72 h [51] . So, AVP receptors may play an important role in the formation of edema after ICH through reduced BBB permeability or AQP4 levels, but the details of the mechanism are still unknown [52] . An in vivo microdialysis study shows that glutamate, taurine and asparagines accumulate transiently in extracellular fluids in the perihematoma region during the early period of ICH.…”
Section: Rbc Lysis Productionmentioning
confidence: 99%
“…Also, pretreated rats with PQQ significantly reduce the production of ROS after ICH, probably due to its antioxidant effects [96] . SR49059, an AVP V(1a) receptor competitive antagonist is proved to have a function of reducing brain edema and neurobehavioral deficits after ICH by decreasing the BBB disruption and AQP4 levels [51,52] . Animal experiments demonstrated that granulocyte-colony stimulating factor can protect ICH by reducing BBB permeation, cell apoptosis and brain edema [97] .…”
Section: Other Medicinesmentioning
confidence: 99%
“…V1a antagonists have also been examined in animal models for the treatment of other disease states such as heart failure, cerebral vasospasm, brain edema, and gastric ulcers (294,322,549). Furthermore, in vitro studies have suggested a potential clinical application for V1a antagonists in treating cancer or renal disease (266,399,479).…”
Section: B V1a and V1b Receptor Antagonistsmentioning
confidence: 99%
“…It should be noted that a part of the intracranial artery causes vasodilatation upon AVP stimulation in an endothelium-dependent manner (264,386 Cerebral edema is a devastating consequence of brain injury that leads to compromised cerebral blood flow and worsening parenchymal damage. Blockade of the V1a receptor by SR49059 has been shown to significantly reduce intracranial pressure or cerebral edema after cortical contusion injury, intracerebral hemorrhage injury, or cerebral artery occlusion in animal models (275,322,384,457,487). Likewise, the V1a/V2 receptor antagonist YM087 (conivaptan) significantly reduced intracranial pressure and cerebral edema after traumatic brain injury (122,168).…”
Section: Cerebral Vasospasm and Brain Edemamentioning
confidence: 99%
“…A study investigating the inhibition of the arginine vasopressin (AVP) V1 receptor in mice after ICH, could thereby demonstrate a significant reduction in cerebral edema formation and significantly less neurobehavioral deficit in the mice treated with the competitive receptor antagonist [89]. They suggest AVP might be a key player of water homeostasis in the brain.…”
Section: Selection Of Most Interesting Candidatesmentioning
confidence: 99%